Solar Dependence of Equatorial F Region Irregularities Observed by COSMIC Radio Occultations. Issue 11 (22nd November 2018) - Yu, Tao; Miyoshi, Yasunobu; Xia, Chunliang; Zuo, Xiaomin; Yan, Xiangxiang; Yang, Na; Sun, Yangyi; Yue, Xinan; Mao, Tian
Abstract: With an improved method for retrieving the equatorial F region irregularities (EFIs) from radio occultation measurements, a huge amount of S4 index profiles from Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellites is employed to study the solar cycle variation of global EFIs during the period of 2007 to 2017. This full solar cycle data show that impacts of the solar activity on the occurrence rates and heights of EFIs are notable and complex. The occurrence rates of EFIs at higher altitude (greater than 500 km) increase with increasing the solar activity. The mean heights ( h ~ ) and heights standard deviation (σ h ) of EFIs at higher altitudes do not show clearly the solar activity dependence. On the other hand, the occurrence rates of EFIs at entire altitudes (from 150 to 800 km) do not have clear relation with the solar activity. The h ~ and σ h of EFIs at entire altitudes increase with increasing the solar activity. Moreover, the dependence of the occurrence rates of EFIs on the solar activity are the strongest in the equinoxes, weaker in winter and weakest in summer. The electric fields and corresponding seasonal variation can account for the EFIs occurrence and height variation versus solar activities, and the EFIs at low altitudes seem to be related to the seed associated with atmospheric gravity wave. Plain Language Summary: The performance of EFIs changes with solar activity is complex. The solar dependence of EFIs seems to be inconsistent when using different observation, i.e. the ground‐base observation indicates no solar dependence, but space‐based observation indicates very good solar dependence. We suppose that this may be due to the fact that EFI at different altitudes is has different solar dependence. For the first time in this article, we have distinguished the information of the height of the EFIs. This is the great advantage of the COSMIC occultation data. After distinguishing the heights, it was found that the occurrence of EFIs above 500 km was well correlated with solar activity, and the correlation between the entire height of EFIs and solar activity was weak. The results of this study are a good explanation of the reasons for the inconsistency of the previous researcher's EFIs solar dependence study. Key Points: We use COSMIC occultation data statistical studies on climatological characteristics of the global EIFs The occurrence of EFIs above 500 km was well correlated with solar activity The correlation between the entire height of EFIs and solar activity was weak